Technology and child development: Evidence from the one laptop per child program - Julián P. Cristia; Pablo Ibarrarán; Santiago Cueto; Ana Santiago; Eugenio Severín (Institute for the Study of Labor (IZA), 2012)
Although many countries are aggressively implementing the One Laptop per Child (OLPC) program, there is a lack of empirical evidence on its effects. This paper presents the impact of the first large-scale randomized evaluation of the OLPC program, using data collected after 15 months of implementation in 319 primary schools in rural Peru. The results indicate that the program increased the ratio of computers per student from 0.12 to 1.18 in treatment schools. This expansion in access translated into substantial increases in use both at school and at home. No evidence is found of effects on enrollment and test scores in Math and Language. Some positive effects are found, however, in general cognitive skills as measured by Raven's Progressive Matrices, a verbal fluency test and a Coding test.
urn:nbn:de:101:1-201206146863
Keywords: C93; I21; I28; 330; education; technology; experiments; Bildungspolitik; Personal Computer; Computerunterstützung; Wirkungsanalyse; Kinder; Kognition; Peru